Effect of laparoscopic sleeve gastrectomy on blood sugar and blood pressure - Al-Basri, Rida J. (AL-Kindy College Medical Journal, 2019)
Background: Surgery is one and may be the most effective method to treat obesity. In the last decade, Laparoscopic Sleeve Gastrectomy is perceived to be less invasive, technically simple, less morbid and more popular form of bariatric surgery. Objectives: This study aims to assess the effect of Laparoscopic Sleeve Gastrectomy on Fasting Blood Glucose Levels and Blood Pressure. Methods: A prospective controlled study in which 50 obese patients were involved, 36 of patients have hypertension and type 2 diabetes mellitus , 7 patients have type 2 diabetes mellitus only, and 7 patients don’t have hypertension or type 2 diabetes. All patients were submitted to Laparoscopic Sleeve Gastrectomy at Al-Kindy Teaching Hospital between October 2014 and October 2016. Results: Forty five of patients were females, while five were males . Mean age was 34 years, mean height 159 cm mean pre Laparoscopic Sleeve Gastrectomy weight was 121kg. Mean post- Laparoscopic Sleeve Gastrectomy weight was 82kg. Mean weight loss outcome at 1 year follow-up is 32.23% of total body weight. . Preoperative initial mean value of fasting blood glucose was 157.4 mg/dL and the declining occurred at 12 months after Laparoscopic Sleeve Gastrectomy was 97 mg/dL . The hypertension remission rates 1 year after Laparoscopic Sleeve Gastrectomy ranges up to 54% of total number of patients and 75% of those with Hypertension. Conclusions: Laparoscopic Sleeve Gastrectomy has an effect in improving Fasting Blood Glucose Levels and Blood Pressure.